Bioremediation efficiency of heavy metal contaminated soil using earthworm Eisenia Fetida - Kniuipytė, Inesa; Praspaliauskas, Marius; Žaltauskaitė, Jūratė; Dikšaitytė, Austra (International Conference “Environmental Engineering”, 2020)
The amount of sewage sludge (SS) used in agriculture and forest plantations is constantly growing in EU. It’s known that even after various treatment methods some of contaminants still remain. The main risks of using SS in agriculture or forestry are related with hevy metals and organic pollutants content in SS. Heavy metals tend to acumulate in the environment and living organisms and may cause different adverse effects. Bioremediation using earthworms can be used to eliminate or mitigate the threat of heavy metals. Bioremediation is cheaper, requiries less energy and is more environmentally friendly than conventional physical or chemical remediation methods. But it’s really important to evaluate bioremediation efficiency for SS, because there is evidence that nutrients in SS might improve efficiency of bioremediation. In this study earthworms Eisenia fetida were exposed for 9 weeks to SS amended soil. Earthworm mortality, growth and heavy metals (Al, Fe) accumulation were evaluated. The results showed that SS had a highly significant effect on earthworm mortality (F=4.98; p